Tocotrienols: Dietary Supplements for Chronic Obstructive Pulmonary Disease - Xiangming Ji; Hongwei Yao; Maureen Meister; Douglas S. Gardenhire; Huanbiao Mo (MDPI AG, 2021)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death worldwide. Emphysema and chronic bronchitis are the two major phenotypes of COPD, which have many symptoms, such as dyspnea, chronic cough, and mucus overproduction. Emphysema is characterized by the destruction of the alveolar wall, while chronic bronchitis is characterized by limitations in expiratory airflow. Cigarette smoking is the most significant risk factor for the pathogenesis of COPD in the developed world. Chronic inflammation contributes to the onset and progression of the disease and furthers the risk of comorbidities. Current treatment options and prevention strategies for COPD are very limited. Tocotrienols are a group of vitamin E molecules with antioxidant and anti-inflammatory properties. Individual tocotrienols (α, γ, and δ) have shown their ability to attenuate inflammation specifically via suppressing nuclear factor-κB-mediated cytokine production. The δ- and γ-forms of tocotrienols have been indicated as the most effective in the prevention of macrophage infiltration, production of reactive oxygen species, and cytokine secretion. This review briefly discusses the pathogenesis of COPD and the role of inflammation therein. Furthermore, we summarize the in vitro and in vivo evidence for the anti-inflammatory activity of tocotrienols and their potential application to COPD management. Coupled with the bioavailability and safety profile of tocotrienols, the ability of these compounds to modulate COPD progression by targeting the inflammation pathways renders them potential candidates for novel therapeutic approaches in the treatment of COPD patients.